Auditory brainstem response (ABR) profiling in schizoaffective disorder. Issue 4 (17th August 2020) - Juselius Baghdassarian, Eva; Lewander, Tommy
Abstract: Objective: The aim of the study was to assess whether the auditory brainstem response (ABR) profiling test for schizophrenia (SZ) would recognise schizoaffective disorder (SZA) patients as SZ or not. Method: Male and female SZA patients ( n = 16) from the psychosis unit at Uppsala University Hospital were investigated. Coded sets of randomised ABR recordings intermingled with patients with SZ, adult attention-deficit hyperactivity disorder (ADHD) and healthy controls were analysed by an independent party blinded to clinical diagnoses. Results: The ABR profiling test for SZ was positive in 5/16 patients (31%) and negative in 11/16 patients (69%) with SZA. A surprising finding was that 4/16 (25%) SZA patients were positive for the ABR profiling test for ADHD. Conclusion: With the ABR profiling test, a minority of patients with SZA tested positive for SZ. In contrast, a majority (85%) of patients with SZ in a previous study tested positive. These preliminary results leave us ignorant whether SZA should be regarded as a SZ-like disorder or a psychotic mood disorder and add to the questions regarding the validity of this diagnostic entity. However, the ABR profiling method is still in its infancy and its exploration in a range of psychiatric disorders is warranted.